Job Environment Factors Influencing Employees’ Performance Competency of Finance Department in Luang Prabang - Panyasavath, Thilana; Keoboualapheth, Soulideth; Indavong, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this research was to study the employees’ operational competency level of the Finance Department of Luang Prabang Province; to study the employees’ opinions towards on the environmental factors in the operation; and to study the job environmental factors influencing employees’ performance competency of Finance Department of Luang Prabang Province. The population used in the research was the employees of the Finance Department of Luang Prabang province with a total sample group of 49 people as a specific random sampling method. The instrument used in the research was a questionnaire with a reliability value equal to 0.970. The statistics used in the data analysis were frequency value, mean value, standard deviation value, correlation coefficient and multiple regression coefficient. The results of the study were found that: The employees’ performance competency was at a high level, including competency in terms of basic characteristics (individual competency), the operation knowledge competency and the competency of working skills. The employees’ opinions towards on the environmental factors were at most important level to the performance of the employees, including the safety and security at work, personal characteristics, social characteristics of work, opportunities for advancement in work, communication, specific characteristics of work, structure, and management of work within the organization and working conditions. For the factors of wages and welfare or other benefits received were at moderate importance level. The job environment Factors had a positive influence on the competency of employees to work were include Personal characteristics that was influence the knowledge of the work of employees, specific characteristics of the work, working conditions and personal characteristics was affect the skills in the work of employees, and the factors of opportunities for advancement in work, security and personal characteristics was affect the basic characteristics of the work of employees. For factors that have a negative impact on the ability of employees to work were include wages, welfare or other benefits received affect the knowledge and skills of employees and the structure, management within the organization affects the competency of employees to work